Targeting Inflammation Driven by HMGB1 - Yang, Huan; Wang, Haichao; Andersson, Ulf (Frontiers in Immunology, 2020)
High mobility group box 1 (HMGB1) is a highly conserved, ubiquitous protein present in the nucleus and cytoplasm of nearly all cell types. It is a multi-facet protein with functions both inside and outside of cells. Extracellular HMGB1 is best known for its prototypical alarmin functions activating innate immunity, after being actively released from cells or passively released upon cell death. Disulfide HMGB1 is an endogenous activator of the TLR4/MD-2 receptor complex and there is significant therapeutic interest in the concept of preventing HMGB1-TLR4-mediated pathology. HMGB1/MD-2 binding can be selectively targeted without disturbing the LPS/MD-2 interactions needed for protection from gram-negative infection. Another important therapeutic strategy is based on the administration of extracellular HMGB1 antagonists preventing RAGEmediated internalization of HMGB1-bound ligands capable of activating endosomal and cytosolic receptor systems. Here we give an abridged review on the role of HMGB1 in inflammation, with a focus on the recent findings on its mission as a damage-associated molecular pattern (DAMP) molecule sensing and mediating danger and as a therapeutic target in inflammatory conditions. Recently generated HMGB1-specific inhibitors in the treatment of inflammatory diseases are discussed.